KAJIAN HUKUM TINDAK PIDANA PEMBUNUHAN YANG DILAKUKAN TERHADAP SESAMA ANGGOTA KEPOLISIAN (Studi Kasus Penembakan terhadap Anggota Detasemen Khusus 88 Anti Teror oleh Dua Rekan Kerja) - Sugeng Riyadi (IBLAM Law Review)
In an effort to maintain state order and protect all people from various forms of crime and violations, the state has the right to impose criminal sanctions on anyone, including members of the Police who are actually law enforcers. The behavior of Polri members is also often scrutinized and criticized in relation to their professionalism in carrying out their duties due to several internal and external factors. This study aims to find out the aspects of criminal law in cases of murder committed jointly by two members of the National Police. The type of research used in this research is legal research, namely legal research whose object of study includes active legal regulations based on library research. The approaches used are the statute approach, conceptual approach, and case approach. Based on the results of the research, it was concluded that with regard to criminal responsibility, the two perpetrators received the same punishment if both were proven to have committed the crime of murder as stipulated in Article 338 of the Criminal Code in conjunction with Article 55 of the Criminal Code, both the main perpetrator and the perpetrator participating. However, a second perpetrator who is not an executor can also be charged under Article 56 of the Criminal Code if his role is only limited to providing assistance at the time of an assassination attempt or deliberately allowing the perpetrator to kill the victim without any attempts at mediation. With regard to criminal acts committed by members of the Indonesian National Police, there is a mechanism for Enforcing the Police Professional Code of Ethics apart from proceedings in the general courts. So for crimes with the threat of 5 years and above, the legal consequences are serious violations with sanctions of dishonorable dismissal.